Isolation of antibacterial compounds from dichloromethane fraction of Malaysian sponges Neopetrosiaexigua - Qaralleh, Haitham; Syed Osman Idid, Syed Zahir Idid; Saad, Shahbudin; Darnis, Deny Susanti (2010)
This study was carried out to isolate the active antibacterial compounds from marine sponge Neopetrosiaexigua. Using disc diffusion methodm methanol extract of N. exigua showed significant antibacterial activity (The inhibition zone against Staphylococcus aureus was 19.5 mm). sequesntially, liquid-liquid extraction was performed using solvenants with different polarity (n-hexane, carbon tetrachloride, dicholoromathane, n-butanol and water in order to isolate the active antibacterial compounds. Bassed on the biological guided fractionation results, dichloromathane and n-butanol fractions showed the hisgest antimicrobial activity. Purification of dichloromathane fraction was done by using SephadexLH-20, normal phase column chromatographyand reverse phase column chromatography to yeild three compounds (1-3). All compounds were tested for their antibacterial activity against Staphyloccus aureus. The results showed that 3 exhibited significant antibacterial activity. Research is still in progress to elucidate the structures of the islated compounds.